Estrategias de marketing y comunicación de la fundación nuevo - Jara Sarcos, Meledy Yamileth (2023)
The case study focuses on the marketing and communication strategies of the Nuevo Amanecer Foundation (FNA), a non-profit organization. The context reveals the critical importance of effective communication in nonprofit organizations, as this communication not only conveys information, but also builds emotional connections and mobilizes community support and donations. The SWOT analysis highlights FNA's strengths, such as its clear mission and experience, along with the opportunities offered by digital marketing and strategic alliances. However, weaknesses are identified, including ineffective past strategies and resource limitations, and threats such as public mistrust and competition. A community survey reveals a high level of knowledge and support for the FNA, with the majority of respondents familiar with the organization and actively participating in its activities. The study emphasizes the need for the FNA to adapt its marketing and communication strategies to take advantage of digital marketing opportunities and diversify its audience. It also focuses on improving the quality of communication, transparency and impact measurement. The support and positive perception of the community is evident, underscoring the importance of maintaining and strengthening these emotional connections for the continued success of the Nuevo Amanecer Foundation in its quest to generate a positive impact on society.